X-ray emission from stellar jets by collision against high-density molecular clouds: an application to HH 248 - López Santiago, J. (2015)
We investigate the plausibility of detecting X-ray emission from a stellar jet that impacts a dense molecular cloud, a scenario that may be typical for classical T Tauri stars with jets in dense star-forming complexes. We first model the impact of a jet against a dense cloud using two-dimensional axisymmetric hydrodynamic simulations, exploring different configurations of the ambient environment. Then, we compare our results with XMM-Newton observations of the Herbig-Haro object HH 248, where extended X-ray emission aligned with the optical knots is detected at the edge of the nearby IC 434 cloud. Our simulations show that a jet can produce plasma with temperatures up to 107 K, consistent with production of X-ray emission, after impacting a dense cloud. We find that jets denser than the ambient medium but less dense than the cloud produce detectable X-ray emission only at impact with the cloud. From an exploration of the model parameter space, we constrain the physical conditions (jet density and velocity and cloud density) that reproduce the intrinsic luminosity and emission measure of the X-ray source possibly associated with HH 248 well. Thus, we suggest that the extended X-ray source close to HH 248 corresponds to a jet impacting a dense cloud.